An eCUA model for integrated computing power and decentralized digital identity and a new business system supporting information framework - Wen QIAO; Xiaozheng WANG; Gan REN; Aidong YANG; Shoufeng WANG; Peng WANG; Xiaozhou YE; Ye OUYANG (Dianxin kexue)
An enhanced customer-user-account (eCUA) model was proposed.Based on the traditional three-household (customer, user, account) model in telecom industry, an enhanced customer-user-account model and its information framework was constructed by means of virtual digital human and decentralized identity technology, combined with the service demand of task-based computing power.With the globally unique identity, eCUA enables the traditional three-household model to have distributed and decentralized sharing capability.eCUA can solve the problem of information inconsistency in multi-account management, multi-source data synchronization, and multi-channel display of same-origin data.It can effectively support the closed-loop management of the whole process of computing power network business, such as computing power subscription, experience, ordering, and transaction operation.Therefore, the eCUA model proposed can be used as the main data reference frame of the integrated telecommunications service support system.